Results of the Technical and Technological Analysis of the Wares from the Novoilyinskiy Culture Sites of the Lower Kama Region - Olga V. Andreeva (Археология евразийских степей)
For the first time, a technical and technological analysis of the ceramics of the Novoilyinskiy culture was carried out within the historical and cultural approach proposed by A.A. Bobrinsky. 163 vessels from the sites of the Lower Kama region were studied using a binocular microscope: Tatar Azibey II, Russian Azibey I, Dubovaya Grivna II and Igim. The research focuses on the preparatory stage of creating ceramics: the selection and processing of raw materials, as well as the creation of a molding mass. During the analysis, it was revealed that at the campsites presented, ceramics of the Novoilyinskiy culture were made mainly from silty clay, and raw materials were preferred to be used not sanded. Potters used the initial plastic raw materials in a naturally moistened state to prepare the molding mass, without using crushing, however, crushing was practiced at the Sauz II campsite (published earlier). The tradition of making a molding mass on the monuments of the Lower Kama region for the population of the Novoilyinskiy culture is stable, the main recipe is IPRM + organic solution + grog, which reflects the formation of cultural traditions among the population.